Strategies To Improve Financial Technology Literacy For Millennials And Generation Z - Putri, Rizki Audina; Ishak, Khodijah (JPS (Jurnal Perbankan Syariah), 2024)
This study analyses the problems and priorities of strategies to improve financial technology literacy, especially among Millennials and Generation Z. This mixed method study uses the analytic network process (ANP) approach. The data sources used are primary and secondary data. Interviews, questionnaires, and literature carried out data collection techniques. Interviews and questionnaires were conducted with seven informants: one regulator, three academics, and three online loan users. The study results showed that the geometric mean determined the priority of fintech literacy problems. The prioritized aspects are the need for more public understanding of online loans, interest rates, and community needs. The priority strategy in improving fintech literacy among Millennials and Generation Z in Bengkalis Regency is to carry out Sharia literacy regarding online loans, regulate online loan interest rates, and reduce the community's need for online loans. Theoretically, this study strengthens the validity of the trade-off theory and provides new insights into strategies to improve fintech literacy. Practically, it contributes to providing strategies to improve fintech literacy for stakeholders.